2010
DOI: 10.4315/0362-028x-73.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Microbial Growth and Enrichment of γ-Aminobutyric Acid during Germination of Brown Rice by Electrolyzed Oxidizing Water

Abstract: Electrolyzed oxidizing water (EOW) has been regarded as a potential environmentally friendly broad spectrum microbial decontaminant. EOW with a pH of 3.0 and oxidation reduction potential of 1,079.0 mV were generated by the electrolysis of a dilute NaCl solution (20 mM) in an electrochemical cell. The effects of EOW, 1% NaClO solution, and alkaline electrolyzed water on controlling microbial growth, germination ratio, and enrichment of gamma-aminobutyric acid in germinated brown rice (GBR) were evaluated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…This work indicated that soaking was more effective than rinsing for decreasing the counts of all the naturallyoccurring microorganisms tested, agreeing with previous research by Lu et al (2010). One possible explanation could be that during rinsing, no effective contact can be achieved between the mung bean sprouts and the AEW, but soaking can guarantee a much more effective contact between them.…”
Section: Effect Of Cleaning Methods On the Disinfection Efficacy Of Asupporting
confidence: 90%
“…This work indicated that soaking was more effective than rinsing for decreasing the counts of all the naturallyoccurring microorganisms tested, agreeing with previous research by Lu et al (2010). One possible explanation could be that during rinsing, no effective contact can be achieved between the mung bean sprouts and the AEW, but soaking can guarantee a much more effective contact between them.…”
Section: Effect Of Cleaning Methods On the Disinfection Efficacy Of Asupporting
confidence: 90%
“…AEW is commonly used in the agricultural and medical fields as a disinfectant for farm and food hygiene (Fabrizio and Cutter, 2004;Northcutt et al, 2007;Guentzel et al, 2008;Cao et al, 2009;Park et al, 2009;Lu et al, 2010;Rahman et al, 2010Rahman et al, , 2011. It is also widely used for the disinfection of medical instruments such as dialyzers (Tanaka et al, 2000), endoscopes (Lee et al, 2004), and dentures (Nagamatsu et al, 2001) because of its potent antimicrobial potential (Kiura et al, 2002;Sharma and Demirci, 2003;Nisola et al, 2011;Rodriguez-Garcia et al, 2011;Feliciano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Slightly AEW has been an authorized food additive in Japan since 2002 because of its proven biological safety and effectiveness as a bactericide even at low available chlorine concentrations (ACC) of 10e30 mg/L and pH 5.0e6.5 (Suzuki, Nakamura, Doi, Kokubo, & Tomita, 2005). Although research has been conducted on the application of electrolyzed water to sprout production (Liu, Hao, Liu, & Li, 2011;Lu et al, 2010), there has been no specific research on the effects of SAEW on GBR production.…”
Section: Introductionmentioning
confidence: 99%